BODY IMAGE REFLECTED IN KELLY LOUISE GOING’S FAT KID RULES THE WORLD - Sunahnik Fitauli; Linusia Marsih (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
Abstract. This study discusses about body image undergone by a seventeen year old boy named Troy, the main character in K. L. Going’s novel Fat Kid Rules the World. The study focuses on Troy’s perception of his body. Qualitative research is applied in this study due to the fact that this study provides understanding into the problems through description. In addition, psychological approach is employed as this study deals with the psychological motivation of the main character in the novel. From the analysis it is found that Troy has negative body image which consists of three areas, namely belief in being heavy, belief in look, and feeling about how people regard his physical structure and look. His negative body image is caused by his negative thoughts and feelings about the size of his body which he believes is huge and ugly so that people always look at him and make fun of his size. Based on the analysis it can be concluded that negative body image could be avoided by developing positive thought and feeling about one’s body . One should not value oneself on the basis of physical appearance but on the basis of achievement. Keywords: body image, perception, Fat Kid Rules the World